Advanced Issues in springback - Wagoner, Robert H.; Lim, Hojun; Lee, Myoung-Gyu (International journal of plasticity, 2013)
► Plastic constitutive equations. ► Variable Young’s modulus. ► Through-thickness integration of stress. ► Magnesium. ► Advanced high strength steels (AHSS). For purposes of this review, springback is the elastically driven change of shape of a metal sheet during unloading and following forming. Scientific advances related to this topic have accelerated dramatically over roughly the last decade, since the publication of two reviews in the 2004–2006 timeframe (Wagoner, 2004; Wagoner et al., 2006). The current review focuses on the period following those publications, and on work in the first author’s laboratory. Much of this recent work can be categorized into five main topics.(1)Plastic constitutive equations(2)Variable Young’s modulus(3)Through-thickness integration of stress(4)Magnesium(5)Advanced high strength steels (AHSS) The first two subjects are related to accurate material representation, the third to numerical procedures, and the last two to particular classes of sheet materials. The principal contributions in these areas were summarized and put into context.